2019
DOI: 10.15171/icnj.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of MindfulnessBased Stress Reduction Group Therapy With Acceptance and Commitment Therapy on Severity of Pain and Health-Related Quality of Life in Patients With Migraine

Abstract: Background: Considering the prevalence of migraine and its detrimental effects on functioning, physical health, and quality of life as well as its psychosocial and social risks. The purpose of this study was to compare the effectiveness of mindfulness-based stress reduction treatment with treatment based on acceptance and commitment to the severity of pain and health-related quality of life in migraine patients. Methods: In this study, a semi-experimental design used with pre-test, post-test, a 3-month follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Studies preliminarily have suggested ACT yields small improvements in variables traditionally examined in headache literature (e.g., headache frequency, medication consumption) and notable improvements in functional or process-based factors associated with acceptance-based interventions. [16][17][18] Similarly, studies examining mindfulness for head pain demonstrated improved functional (e.g., activity interference) and process outcomes (e.g., pain catastrophizing, acceptance, and selfefficacy). 19,20 Despite promising results from headache treatment studies, 18,[21][22][23] meta-analytic reviews of mindfulness interventions for head pain draw conflicting conclusions regarding efficacy for reducing headache symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies preliminarily have suggested ACT yields small improvements in variables traditionally examined in headache literature (e.g., headache frequency, medication consumption) and notable improvements in functional or process-based factors associated with acceptance-based interventions. [16][17][18] Similarly, studies examining mindfulness for head pain demonstrated improved functional (e.g., activity interference) and process outcomes (e.g., pain catastrophizing, acceptance, and selfefficacy). 19,20 Despite promising results from headache treatment studies, 18,[21][22][23] meta-analytic reviews of mindfulness interventions for head pain draw conflicting conclusions regarding efficacy for reducing headache symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of literature aims to implement acceptance and commitment therapy (ACT), structured mindfulness interventions (i.e., mindfulness‐based stress reduction [MBSR], and mindfulness‐based cognitive therapy [MBCT]) for head pain. Studies preliminarily have suggested ACT yields small improvements in variables traditionally examined in headache literature (e.g., headache frequency, medication consumption) and notable improvements in functional or process‐based factors associated with acceptance‐based interventions 16–18 . Similarly, studies examining mindfulness for head pain demonstrated improved functional (e.g., activity interference) and process outcomes (e.g., pain catastrophizing, acceptance, and self‐efficacy) 19,20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the point of view of Neff [ 40 ], a pioneer of experimental work, “self-compassion” is having a non-judgmental attitude towards one’s shortcomings, weaknesses, failures, pain, and suffering, not avoiding them, and the desire to reduce pain and suffering and self-heal with kindness. Although self-compassion is associated with psychological outcomes, there are a limited number of studies examining the relationship between self-compassion and QOL in patients whose physical health is threatened [ 41 ], and to the best of our knowledge, only one study showed that higher self-compassion is associated with fewer clinical symptoms of CVD [ 42 ]. In order to understand and clarify the relationship between the structures of SOC, spiritual well-being, and self-compassion with QOL, it seems that one of the most important and effective factors is pain self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, self-compassion is a positive psychological construct characterised by the expansion of being compassionate with oneself, often during periods of suffering. Although self-compassion is associated with psychological outcomes, there are a limited number of studies examining the relationship between self-compassion and QOL in patients whose physical health is threatened [48], and to the best of our knowledge, only one study showed that higher self-compassion is associated with fewer clinical symptoms of CVD [49]. In order to understand and clarify the relationship between the structures of SOC, spiritual well-being, and selfcompassion with QOL, it seems that one of the most important and effective factors is pain self-e cacy.…”
Section: Introductionmentioning
confidence: 99%